BIG DATA for Healthcare: A Survey - Safa Bahri (2019)
Recently, the massification of new technologies, which has been adopted by a large majority of the world population, has accumulated a tremendous amount of data, including clinical data. This clinical data have been gathered up and interpreted by medical organizations in order to gain insights and knowledge useful for clinical decisions, drug recommendations, and better diagnoses, among many other uses. This paper highlights the enormous impacts of big data on medical stakeholders, patients, physicians, pharmaceutical and medical operators, and healthcare insurers, and also reviews the different challenges that must be taken into account to get the best benefits from all this big data and the available applications.